Scrounging in northern-ireland - the beginnings of an investigation - Tipping, B (Economic & Social Studies, 1982)
Precis: This is a report of a cross-sectional survey carried out in Antrim on the registered unemployed to test some aspects of the "scrounger" hypothesis. A brief literature review reveals a lack of empirical evidence on this subject for Northern Ireland and examines some of the assumptions that underpin the major British studies. Two indicators of work shyness are examined for Antrim: the proportion of the unemployed that left their last jobs voluntarily and the minimum income that respondents would accept to work. The results indicate that the extent of malingering amongst the target population does not justify the current attitude of suspicion that pervades the administration of social security services.
Keywords: Economics; Sociology